2001
DOI: 10.1504/ijhtm.2001.001104
|View full text |Cite
|
Sign up to set email alerts
|

Is health information technology investment related to the financial performance of US hospitals? An exploratory analysis

Abstract: Information systems lie at the centre of organized delivery systems, providing opportunities to improve access, outcomes, and quality benefiting consumers, providers, insurers, and purchasers. However, it is unknown whether hospital financial performance improves after investment in these systems. Our study finds that hospitals with integrated information systems had a 1.7% higher total margin and a 1.0% higher operating margin in 1993 than hospitals without integrated information systems. This greater profita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…On the plus side, a 2001 study found that hospitals with integrated information systems were more profitable. 31 Florida hospitals using more information technology had higher revenues and incomes, but higher expenses. 32 A literature review found that the use of an electronic medical record often increases billings but reduces provider productivity by increasing time spent on documentation.…”
Section: Discussionmentioning
confidence: 98%
“…On the plus side, a 2001 study found that hospitals with integrated information systems were more profitable. 31 Florida hospitals using more information technology had higher revenues and incomes, but higher expenses. 32 A literature review found that the use of an electronic medical record often increases billings but reduces provider productivity by increasing time spent on documentation.…”
Section: Discussionmentioning
confidence: 98%
“…Within the United States, early work by Parente and Dunbar [26] used a survey of US hospitals receiving Medicare prospective payment to examine the relationship between a hospital's financial performance and its adoption of integrated information systems. In bivariate analyses, they found that hospitals investing in IT had higher total profit margins, but that the relationship disappeared within the multivariate regression specification.…”
Section: Prior Researchmentioning
confidence: 99%
“…BI is an umbrella term that covers the applications, infrastructure, tools, and best practices that enable organizations to access and analyze information with the aim of improving and optimizing decisions and performance [5]. Notably, a study by Parente and Dunbar shows that healthcare organizations that use HIS have higher operating margins and total margins than organizations without HIS [6].…”
Section: Introductionmentioning
confidence: 99%